MEDICAL ELECTRONICS BASED SMART SHOE FOR BLIND PEOPLE (Journal of Pharmaceutical Negative Results, 2023)
Power of sight is considered as the most important of all senses. Blind people are often dependent on others for their daily tour. Over time several advancements in technology has helped in increasing entertainment and comfort for the blind. “Smart shoe" can assist the blind on their daily routine and can act as a comfortable and safe companion on their journey. Common assistances provided earlier for the blind include walking sticks or guide dogs. It includes ultrasonic sensors with a step counter that can alert the person of the impending obstacles. The technology results can improve their ways of growth and can drive them to lead their independent lives. Medical assistance can be provided depending on the pattern of the walk. The electronic hardware will be fixed in shoes for users. User will wear the shoe and travel anywhere, and attached sensor will be sense obstacles near to the shoes alerts with the help of visually impaired people. India contributes about 21% of the blind people over total population.